Narratives of ice loss: New approaches to shrinking glaciers and climate change adaptation. Issue 125 (October 2021) - Moulton, Holly; Carey, Mark; Huggel, Christian; Motschmann, Alina
Highlights: Competing narratives of ice loss are overlooked in climate change adaptation. Globally relevant case study of glacial lake conflict in Cordillera Blanca, Peru. Narrative analysis as a methodology to understand power and glacier change. Environmental authority can emerge in counterintuitive ways at unexpected times. Results help to understand community resilience and limits of adaptation. Abstract: This article explores an as-yet overlooked component of glacier melt: how competing narratives of ice loss are embedded in divergent climate change adaptation debates. This analysis of regional narratives of ice loss exposes the contested role of glacial meltwater amongst local residents, framing glaciers not just as physical features but also as nodes of discourse and imagination that influence climate change adaptation. Peru's Cordillera Blanca offers an excellent case study for this new narrative approach to shrinking glaciers. The Cordillera Blanca hosts 25 percent of Earth's tropical glaciers, has hundreds of glacial lakes and has generated some of the world's deadliest glacial lake outburst floods (GLOFs). Despite decades of glacial lake management in the Cordillera Blanca, government agencies, researchers, local people and hydroelectric companies often disagree as to how to safely manage these lakes to prevent floods and maintain water security. This study helps explain why they disagree and why social conflict has repeatedly occurred around Lakes Palcacocha and Shallap. It analyzes narratives embedded in local and national newspapers and other media to understand varying views. Frequently, competing visions of glacial lake risk management stem from power structures that prioritize certain narratives over others in response to perceived political and environmental conditions. Thus, narrative analysis offers a methodology to understand local and regional experiences with glacier change and climate adaptation, including how and where environmental authority emerges, with broader implications for a global politics of ice loss.